Multifaceted spiral suture: A hemostatic technique in managing placenta praevia or accrete. Issue 49 (December 2017) - Meng, Yifan; Wu, Peng; Deng, Dongrui; Wu, Jianli; Lin, Xingguang; Beejadhursing, Rajluxmee; Zha, Ying; Qiao, Fuyuan; Feng, Ling; Liu, Haiyi; Zeng, Wanjiang
Abstract : Abstract: Patients with total placenta previa and past history of cesarean delivery often experience overwhelming hemorrhage during childbirth. In order to control intraoperative and postoperative bleeding, we propose a novel multifaceted spiral suture of the lower uterine segment which directly sutures the bleeding site. To evaluate the efficacy and safety of multifaceted spiral suture, a retrospective study was conducted using data from 33 patients with total placenta praevia and caesarean history. All participants underwent multifaceted spiral suture and no patient experienced uncontrollable bleeding or underwent hysterectomy. The average blood loss of all patients involved was 1327.3 ± 1244.1 mL. Five patients reported blood loss exceeding 3000 mL (15.15%), and the highest reached to 4000 mL. No complications such as fever, pyometra, synechiae, or uterine necrosis were observed. Three cases (3/33, 9.09%) reported hematuria in the first 3 days following surgery and spontaneous resolution were observed within 3 to 7 days following insertion of indwelling catheters. No complaints were received during 6-month follow-up visits. These findings suggest that multifaceted spiral suture is a practical, feasible, and promising technique in potentially minimizing postpartum bleeding and avoiding hysterectomy for patients with placenta praevia or accrete. Abstract : Supplemental Digital Content is available in the text